Regulacje upadłościowe w samorządzie terytorialnym - przypadek Węgier - Babczuk, Arkadiusz (Municipal Bankruptcy Law - Case Study: Hungary, 2007)
The subject of this article is Hungarian experience in municipal bankruptcy issues. The author characterizes reasons of excessive debt of some municipalities. Then he presents circumstances that cause creation of municipal bankruptcy law in Hungary. He briefly characterizes Hungarian municipal bankruptcy law. Finally, he presents the efficiency of that law.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 531-540